answersLogoWhite

0


Best Answer

It is 3 terms of an algebraic expression

User Avatar

Wiki User

7y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What is 6x - 9y - 2?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Algebra

How do you factorise 6x-27xy?

6x - 27xy= 3x(2 - 9y)=========


How do you solve 6x-5y equals 22 and 9y plus 7 equals 5x plus 8?

1. 6x - 5y = 22 2. 5x - 9y = -1 1 times 5: 30x - 25y = 110 2 times 6: 30x - 54y = -6 Subtract : 29y = 116, so y = 4 and x therefore = 7


How find y intercept for linear equation -6x - 9y equals -3?

There are at least two algebraic ways. The simple way is to put x = 0 and solve: Thus: -6*0 -9y = -3 that is -9y = -3 or 9y = 3 so that y = 1/3 Rewrite the equation in slope-intercept form (y = mx + c). Thus: -9y = 6x - 3 So that y = -2/3*x + 1/3 and so c = intercept 1/3 The non-algebraic way is to draw the graph and read off the value of the intercept.


What is 9y2 - 25yz - 6z2?

9y**2-25yz-6z**2Multiply first and last terms9*-6=-54Find factors of -542,-27 = 2+-27=-25-2,27 = -2+27=25Rewrite9y**2-27zy+2zy-6z**2Factor pairs of terms9y**2-27zy = 9y(y-3z)2zy-6z**2= 2z(y-3z)9y**2-27zy+2zy-6z**2= 9y(y-3z)+2z(y-3z)Factor:9y(y-3z)+2z(y-3z) = (y-3z)(9y+2z)


Write 8x-9y equals 2 as a function of y?

The question asks for a function of 'y', so we'll show 'x' as a function of 'y':Given: 8x - 9y = 2Add 9y to each side:8x = 2 + 9yDivide each side by 8:x = 2/8 + 9y/8orx = 1/8 (2 + 9y).==================================================If the questioner actually wants to see it in the more familiar form of [ y = a function of x ],we can massage the original equation around to show that as well.Given: 8x - 9y = 2Subtract 8x from each side:-9y = 2 - 8xMultiply each side by -1:9y = 8x - 2Divide each side by 9:y = 8x/9 - 2/9ory = 1/9 (8x - 2)

Related questions

How do you factor 30x2 - 45xy - 10x?

5x(6x + 9y + 2)


How do you factorise 6x-27xy?

6x - 27xy= 3x(2 - 9y)=========


What is 2x plus 9y - 6x?

9y - 4x


How do you solve 2x-3y5 and -6x 9y12 using the linear sombination method?

This system is inconsistent. There is no solution. 2x - 3y = 5 -6x + 9y = 12 Multiply the top equation by 3: 6x - 9y = 15 add the two equations together: 6x - 6x - 9y + 9y = 5 + 12 0 = 17 Which is a contradiction. Therefore the lines never intersect, and the solution is the empty set.


What is the answer to 5x - 4y plus 9y plus x -9 plus 7?

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■


3x plus 6y equals 5 -6x plus 9y equals 4?

3x + 6y = 5 -6x + 9y = 4 multiply by 2 the first equation 2(3x + 6y = 5) -6x + 9y = 4 6x + 12y = 10 -6x + 9y = 4 add both equations 21y = 14 divide by 21 to both sides y = 14/21 simplify y = 2/3 3x + 6y = 5 replace 2/3 with x 3(2/3) + 6y = 5 2 + 6y = 5 subtract 2 to both sides 6y = 3 divide by 6 to both sides y = 1/2 Thus, the solution point is (1/2, 2/3).


What is 6x plus 3y plus 6y-2x?

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y


What is 2x plus 3y plus 4x plus 9y?

To simplify the expression 2x + 3y + 4x + 9y, you first combine like terms. Adding the coefficients of x terms gives 2x + 4x = 6x. Similarly, adding the coefficients of y terms gives 3y + 9y = 12y. Therefore, the simplified expression is 6x + 12y.


How do you find the quadratic function yx2-6x 7?

помогите плиз сократить дробь 3y^2-8y-6/4-9y^2


How many values of x and y satisfy the equations 2x plus 6y equals 12 and 3x plus 9y equals 18?

2X + 6Y = 12 3X + 9Y = 18 try elimination - 3(2X + 6Y = 12) 2(3X + 9Y = 18) - 6X - 18Y = - 36 6X + 18Y = 36 ================= I will say this system is dependent and an infinite number of solutions can be found.


How do you solve 6x-5y equals 22 and 9y plus 7 equals 5x plus 8?

1. 6x - 5y = 22 2. 5x - 9y = -1 1 times 5: 30x - 25y = 110 2 times 6: 30x - 54y = -6 Subtract : 29y = 116, so y = 4 and x therefore = 7


Simplifying rational expressions 6x-5y plus -3x-4y?

(6x - 5y) + (-3x - 4y) =6x - 5y - 3x - 4y =3x - 9y =3 (x - 3y)